The Effectiveness of Syzygium Polyanthum to Reduce Blood Pressure in Elderly with Hypertension - Sari, Surya Mustika; Vidia, Henny (Jurnal MIDPRO, 2024)
Hypertension is often referred to as the "silent killer". The factors that influence blood pressure are age, gender, high salt consumption, environment (stress), obesity, high coffee consumption, and genetics. One effort to treat hypertension is with pharmacological and non-pharmacological treatment, non-pharmacological treatment by giving boiled bay leaf water to lower blood pressure in hypertension sufferers. The aim of this research was to determine the effectiveness of giving brewed bay leaves to reduce blood pressure in elderly people with hypertension in the work area of ​​the Posyandu for the Elderly in Gayaman Village, Mojoanyar District, Mojokerto Regency. The type of research used is a Quasy-experimental research design with the design used One Group Pre-Post Test Design. This attempts to reveal cause and effect by involving groups of brewed bay leaves. The population of this study was 45 elderly people in the working area of ​​the Posyandu for the Elderly in Gayaman Village, Mojoanyar District, the sample taken was 40 respondents using simple random sampling. The independent variable in this study was the administration of brewed bay leaves, the dependent variable was blood pressure. The collected data was then tabulated and analyzed using the Wilcoxon statistical test and t-test with a significance level of 0.05. From the results of this research, it was found that in the brewed bay leaf group, before being given boiled bay leaf water, the average MAP (Mean Arterial Preassure) value was 103.67 and after being given boiled bay leaf water, the average MAP (Mean Arterial Preassure) value was 94.67. So it can be concluded that the results of this study are effective in reducing hypertension by administering brewed bay leaves.